Expression profile of microRNAs in porcine alveolar macrophages after Toxoplasma gondii infection - Senyang Li; Jing Yang; Luyao Wang; Fen Du; Junlong Zhao; Rui Fang (Parasites & Vectors, 2019)
Abstract Background Toxoplasma gondii is an apicomplexan protozoan parasite that can cause serious clinical illnesses in both humans and animals. microRNAs (miRNAs) are non-protein-coding RNAs that can regulate the expression of target genes. A previous study found that many miRNAs were differentially expressed after T. gondii infection and exert significant effects and revealed that both host survival and the virulence of different strains can be regulated by different miRNAs. Macrophages play an important role in T. gondii infection, but few studies have investigated the relationship between miRNAs and porcine alveolar macrophages infected with T. gondii. Methods Porcine alveolar macrophages (3D4-21) were infected with the RH (Type I) and Me49 (Type II) strains of T. gondii for 12 h and 24 h and then harvested. miRNA libraries were generated using the NEBNext® Multiplex Small RNA Library Prep Set for Illumina® (NEB, USA), and the miRNA expression levels were estimated based on transcripts per million reads (TPM). Results Our study generated six miRNA expression profiles from macrophages infected with RH and Me49 compared with the control groups. The comparison of the T. gondii-infected and uninfected samples identified 81 differentially expressed miRNAs, including 36 novel miRNAs and 45 mature miRNAs. The target genes of these differentially expressed miRNAs were predicted using miRanda software, and ssc-miR-127 and ssc-miR-143-3p were predicted to regulate nitric oxide synthase 1 (NOS1) and nitric oxide synthase 3 (NOS3), respectively, which play essential roles in synthesizing nitric oxide (NO) by oxidizing L-arginine. These genes were differentially expressed in both the RH- and Me49-infected groups. A KEGG enrichment analysis indicated that the predicted target genes were involved in multiple signaling pathways, including FcγR-mediated phagocytosis, the AMPK signaling pathway, the mTOR signaling pathway, and the FcγRI signaling pathway, all of which are indispensable for the normal functioning of porcine alveolar macrophages. Conclusions Our results provide data on the miRNA profile of porcine alveolar macrophages infected with T. gondii. To our knowledge, this study provides the first demonstration of the relationship between miRNA and macrophages of swine origin. Understanding the functions of these regulated miRNAs will aid the investigation of T. gondii infectious diseases, and the differentially expressed miRNAs might be candidate drug targets for T. gondii infection in pigs.